Applied Economics - Griffiths, Alan; Wall, Stuart (Harlow : Financial Times/Prentice Hall, 2004)
The book has a broad coverage of economic topics and its unique blend of theory and application, the tenth edition continues the traditions which has established it as the best- selling text for students of applied economics. It communicates the vitality and relevance of the subject to students, bringing economics to life and helping them apply economic principles to the 'real world'. The book is ideal for undergraduates studying economics, business studies, management and the social sciences. It is also suitable for those studying professional courses, HND and A-level courses.
Includes bibliographical references and index.
rpm 18/11/13
Loans
Keywords: Economics; Macroeconomics; International economics